Micro-nano structure carbon fiber felt for flow battery electrode as well as preparation method and application of micro-nano structure carbon fiber felt

Through high-voltage electrospinning and subsequent treatment, the micro-nano structure carbon fiber felt is formed, which solves the problem of insufficient strength and electrochemical performance of the liquid flow battery electrode material, and achieves efficient energy and voltage efficiency improvement.

CN119121504AActive Publication Date: 2024-12-13BAOWU CHARCOAL MATERIAL TECH CO LTD

Patent Information

Application Number
CN202310654743.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-05
Publication Date
2024-12-13
Estimated Expiration
2043-06-05

AI Technical Summary

Technical Problem

The carbon fiber felt of the existing liquid flow battery electrode materials has insufficient strength and electrochemical properties, resulting in strong hydrophobicity on the electrode surface, the electrolyte cannot be well infiltrated, the electrocatalytic activity is poor, and the strength of the nano-scale electrode precursor is average. It is difficult to apply.

Method used

Boron-containing polyacrylonitrile nanofibers are prepared by high-voltage electrospinning. After pre-oxidation, loosening and interruption, mixing, combing, mesh laying, and needle-punching, and finally, through carbonization, graphitization and activation, micro-nano structure carbon fiber felt , reduce resistance and improve electrocatalytic activity.

Benefits of technology

It improves the electrochemical performance of the flow battery, enhances the strength and electrochemical performance of the electrode, improves energy efficiency, voltage efficiency and Coulomb efficiency, and reduces the heat treatment temperature and energy consumption cost of the electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121504A_ABST
    Figure CN119121504A_ABST
Patent Text Reader

Abstract

The invention discloses a micro-nano structure carbon fiber felt for a flow battery electrode as well as a preparation method and application thereof, the preparation method comprises the following steps: S1, adding polyacrylonitrile powder and nano boride into an organic solvent, stirring until the polyacrylonitrile powder and the nano boride are uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers through high-voltage electrostatic spinning; s2, the boron-containing polyacrylonitrile nanofibers are subjected to pre-oxidation treatment and opening and breaking treatment, and boron-containing pre-oxidized nanofiber short filaments are obtained; s3, carrying out mixing, carding, lapping and needling treatment on the boron-containing pre-oxidized nanofiber short filaments and the chopped pre-oxidized filaments to obtain a micro-nano structure pre-oxidized felt; s4, carbonizing, graphitizing and activating the pre-oxidized felt with the micro-nano structure to obtain the carbon fiber felt with the micro-nano structure. The prepared carbon fiber felt with the micro-nano structure has a micro-nano composite structure, has relatively low resistance and relatively high electrocatalytic activity when being used for a flow battery electrode, and can effectively improve the electrochemical performance of a flow battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of liquid flow batteries, and in particular relates to a micro-nanostructured carbon fiber felt for liquid flow battery electrodes, a preparation method and an application thereof. Background Art

[0002] The global energy consumption structure is accelerating its transformation to low-cost, clean renewable energy represented by solar energy, wind energy, hydropower, biomass energy, etc. A large number of renewable energy sources have non-steady-state characteristics of volatility and intermittency, which are affected by factors such as weather. In order to improve the effective utilization rate of new energy and achieve real-time balance between renewable energy generation and load, it is the need of the times to develop efficient and reliable large-scale energy storage technology. Among them, liquid flow batteries have the advantages of high energy conversion efficiency, large storage capacity, free site selection, deep discharge, long service life, safety and environmental protection, and are considered to be one of the most promising large-scale energy storage technologies.

[0003] Polyacrylonitrile-based carbon fiber felt is a key material for liquid flow batteries, providing reactive sites for electrochemical reactions. Currently commercial carbon fiber felt materials are mainly used for fire-resistant and heat-insulating materials. Their surface structure and thickness are not processed and produced based on the characteristics of liquid flow battery electrode materials. Therefore, they cannot fully meet the needs of liquid flow batteries in terms of specifications and performance. If it is used directly in liquid flow batteries, due to the strong hydrophobicity of the electrode surface, it cannot be well infiltrated with the electrolyte, resulting in poor electrocatalytic activity and a certain degree of irreversibility.

[0004] Therefore, it is necessary to develop electrode-specific carbon fiber felt materials for liquid flow battery needs, and it is expected to further improve the energy efficiency and energy density of liquid flow battery products, which is of great significance to accelerate the development of advanced electrochemical energy storage technology and the diversification of clean energy research and development. Chinese patent application No. 201711204113.3 mixes polyacrylonitrile-based carbon fiber and asphalt-based carbon fiber to prepare carbon fiber felt, which reduces production costs, has low bulk resistance and high electrocatalytic activity, but the electrochemical performance after assembling the battery is general; Chinese patent application No. 201110413738.7 adds electrode catalysts such as carbon nanotubes to the composite spinning solution, obtains nanoscale electrode precursors by electrospinning, and then obtains electrode materials with high specific surface area by pre-oxidation and carbonization, but the strength of the integrated nanofiber felt material is general, the nanocarbon fiber filaments are easy to peel off, and the application is difficult. The carbon fiber felt electrode materials prepared by the above methods are still insufficient in strength and electrochemical performance, and need to be further optimized. Summary of the invention

[0005] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a micro-nanostructured carbon fiber felt for liquid flow battery electrodes and a preparation method and application, which can solve the deficiencies of the carbon fiber felt electrode materials in the prior art in terms of strength and electrochemical properties. The micro-nanostructured carbon fiber felt prepared by the present invention has a micro-nano composite structure, and is used for liquid flow battery electrodes with lower resistance and higher electrocatalytic activity, which can effectively improve the electrochemical performance of the liquid flow battery.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A first aspect of the present invention provides a method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode, comprising the following steps:

[0008] S1, adding polyacrylonitrile powder and nano-boride into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers by high-voltage electrospinning;

[0009] S2, pre-oxidizing and opening and breaking the boron-containing polyacrylonitrile nanofibers to obtain boron-containing pre-oxidized nanofiber staples;

[0010] S3, mixing, combing, laying and needle punching the boron-containing pre-oxidized nanofiber short filaments and short chopped pre-oxidized filaments to obtain a micro-nano structure pre-oxidized felt;

[0011] S4, carbonizing, graphitizing and activating the micro-nano structured pre-oxidized felt to obtain a micro-nano structured carbon fiber felt.

[0012] Preferably, in step S1:

[0013] The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.1-20):(500-3000); and / or

[0014] The nano boride is selected from one or more of nano boron nitride, nano boron carbide, nano zirconium boride and nano titanium boride; and / or

[0015] The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; and / or

[0016] The stirring temperature is 30 to 90° C.; and / or

[0017] The high-voltage electrospinning is one of single-needle, multi-needle and needle-free.

[0018] Preferably, in step S1:

[0019] The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.5-10):(800-2000) and / or

[0020] The stirring temperature is 40-80°C.

[0021] Preferably, in step S2:

[0022] The pre-oxidation treatment is carried out in an air atmosphere at 180-300° C. for a treatment time of 0.5-5 h; and / or

[0023] The boron-containing pre-oxidized nanofiber short filaments have a length of 3 to 12 cm and a diameter of 50 to 800 nm.

[0024] Preferably, in step S2:

[0025] In the pre-oxidation treatment, the treatment temperature is 200-280° C. and the treatment time is 1-4 hours; and / or

[0026] The boron-containing pre-oxidized nanofiber short filaments have a length of 5 to 9 cm and a diameter of 100 to 600 nm.

[0027] Preferably, in step S3:

[0028] The weight ratio of the boron-containing pre-oxidized nanofiber short filaments to the short chopped pre-oxidized filaments is 10:90 to 90:10; and / or

[0029] The chopped pre-oxidized yarn is selected from one or more of polyacrylonitrile-based pre-oxidized yarn, asphalt-based pre-oxidized yarn and viscose-based pre-oxidized yarn; and / or

[0030] The thickness of the micro-nano structure pre-oxidation felt is 2 to 10 mm.

[0031] Preferably, in step S3:

[0032] The weight ratio of the boron-containing pre-oxidized nanofiber short filaments to the short chopped pre-oxidized filaments is 20:80 to 80:20; and / or

[0033] The thickness of the micro-nano structure pre-oxidation felt is 3-8 mm.

[0034] Preferably, in step S4:

[0035] The carbonization process is carried out in a nitrogen atmosphere, the carbonization temperature is 600-1600° C., and the carbonization time is 0.5-4 h; and / or

[0036] The graphitization process is carried out in a nitrogen atmosphere, the graphitization temperature is 1800-3000° C., and the graphitization time is 0.5-4 h; and / or

[0037] The activation process is carried out in an activation gas atmosphere, the activation temperature is 500-1500° C., and the graphitization time is 0.5-5 h; and / or

[0038] The thickness of the micro-nano structure carbon fiber felt is 1 to 8 mm.

[0039] Preferably, in step S4:

[0040] During the carbonization process, the carbonization temperature is 700-1500° C. and the carbonization time is 1-3 hours; and / or

[0041] During the graphitization process, the graphitization temperature is 1900-2800° C., and the graphitization time is 1-3 hours; and / or

[0042] During the activation process, the activation gas is carbon dioxide or water vapor, the activation temperature is 600-1200° C., and the graphitization time is 1-4 hours; and / or

[0043] The thickness of the micro-nano structure carbon fiber felt is 2-6 mm.

[0044] The second aspect of the present invention provides a micro-nanostructured carbon fiber felt for liquid flow battery electrodes prepared according to the method for preparing the micro-nanostructured carbon fiber felt for liquid flow battery electrodes described in the first aspect of the present invention.

[0045] The third aspect of the present invention provides an application of micro-nanostructured carbon fiber felt for liquid flow battery electrodes prepared according to the preparation method of micro-nanostructured carbon fiber felt for liquid flow battery electrodes described in the first aspect of the present invention in liquid flow battery electrodes.

[0046] Preferably, the flow battery electrode is made of micro-nanostructured carbon fiber felt at a current density of 120 mA / cm 2 When the energy efficiency is ≥83%, the voltage efficiency is ≥84%, and the coulombic efficiency is ≥97%; and / or

[0047] The flow battery electrode is made of micro-nanostructured carbon fiber felt at a current density of 200 mA / cm 2 When the energy efficiency is ≥80%, the voltage efficiency is ≥81%, and the coulombic efficiency is ≥97%.

[0048] The micro-nanostructured carbon fiber felt for flow battery electrodes provided by the present invention and its preparation method and application have the following beneficial effects:

[0049] 1. The micro-nano structured carbon fiber felt prepared by the present invention has both nano-scale carbon fiber and micron-scale carbon fiber, forming a micro-nano gradient pore structure, effectively improving the porosity and reducing the resistance, and improving the energy efficiency, voltage efficiency, coulomb efficiency and electrolyte utilization rate of the flow battery;

[0050] 2. The present invention adds nano-boride to the spinning solution to evenly disperse the boron element in the boron-containing polyacrylonitrile fiber, thereby improving the catalytic graphitization effect of boron, reducing the graphitization temperature, and increasing the degree of graphitization, so that the pre-oxidized felt can be carbonized and graphitized at a relatively low heat treatment temperature, thereby greatly saving energy consumption costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0052] Figure 1 The present invention is a schematic flow chart of a method for preparing micro-nanostructured carbon fiber felt for liquid flow battery electrodes. DETAILED DESCRIPTION

[0053] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.

[0054] Combination Figure 1 As shown, a method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode of the present invention comprises the following steps:

[0055] S1, adding polyacrylonitrile powder and nano-boride into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers by high-voltage electrospinning;

[0056] Specifically, polyacrylonitrile powder, nano-boride and organic solvent are prepared in a weight ratio of 100:(0.1-20):(500-3000), polyacrylonitrile powder and nano-boride are added to the organic solvent, stirred at 30-90°C until uniformly dissolved, to form a spinning solution, and boron-containing polyacrylonitrile nanofibers are prepared by high-voltage electrostatic spinning. In a specific embodiment, the weight ratio of polyacrylonitrile powder, nano-boride and organic solvent is 100:(0.5-10):(800-2000); in a further preferred embodiment, the weight ratio of polyacrylonitrile powder, nano-boride\organic solvent is 100:(2-5):(900-1600). The nano boride is selected from one or more of nano boron nitride, nano boron carbide, nano zirconium boride and nano titanium boride; the organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; the stirring temperature is 40-80°C; and the high-voltage electrospinning is one of single needle, multi-needle and needleless.

[0057] S2, pre-oxidizing and opening and breaking the boron-containing polyacrylonitrile nanofibers to obtain boron-containing pre-oxidized nanofiber staples;

[0058] Specifically, the boron-containing polyacrylonitrile nanofiber obtained in step S1 is subjected to a pre-oxidation treatment in an air atmosphere at 180-300° C. for 0.5-5 hours, and then subjected to an opening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 3-12 cm and a diameter of 50-800 nm. In a specific embodiment, during the pre-oxidation treatment, the treatment temperature is 200-280° C., and the treatment time is 1-4 hours; the length of the obtained boron-containing pre-oxidized nanofiber short filaments is 5-9 cm, and the diameter is 100-600 nm.

[0059] S3, mixing, combing, laying and needle punching the boron-containing pre-oxidized nanofiber short filaments and the short pre-oxidized filaments to obtain a micro-nano structure pre-oxidized felt;

[0060] Specifically, the boron-containing pre-oxidized nanofiber staples and short-cut pre-oxidized fibers obtained in step S2 are mixed, combed, laid, and needled at a weight ratio of 1:9 to 9:1 to obtain a micro-nano structure pre-oxidized felt with a thickness of 2 to 10 mm. In a specific embodiment, the weight ratio of the boron-containing pre-oxidized nanofiber staples and the short-cut pre-oxidized fibers is 1:4 to 4:1; in a further embodiment, the weight ratio of the boron-containing pre-oxidized nanofiber staples and the short-cut pre-oxidized fibers is 7:13 to 7:3. The short-cut pre-oxidized fibers are selected from one or more of polyacrylonitrile-based pre-oxidized fibers, asphalt-based pre-oxidized fibers, and viscose-based pre-oxidized fibers. The thickness of the micro-nano structure pre-oxidized felt is 3 to 8 mm.

[0061] S4, carbonizing, graphitizing and activating the micro-nano structured pre-oxidized felt to obtain the micro-nano structured carbon fiber felt.

[0062] Specifically, the micro-nanostructure pre-oxidized felt obtained in step S3 is carbonized in a nitrogen atmosphere at 600-1600°C for 0.5-4h, graphitized in a nitrogen atmosphere at 1800-3000°C for 0.5-4h, and activated in an activated gas atmosphere at 500-1500°C for 0.5-5h to obtain a micro-nanostructure carbon fiber felt with a thickness of 1-8mm. In a specific embodiment, during the carbonization process, the carbonization temperature is 700-1500°C (preferably 800-1200°C), and the carbonization time is 1-3h (preferably 1.5-2h); during the graphitization process, the graphitization temperature is 1900-2800°C (preferably 2000-2300°C), and the graphitization time is 1-3h (preferably 1.5-2h); during the activation process, the activation gas is carbon dioxide or water vapor, the activation temperature is 600-1200°C (preferably 700-950°C), and the graphitization time is 1-4h (preferably 1-2.5h). The thickness of the micro-nanostructured carbon fiber felt is 2-6mm.

[0063] The present invention also provides a micro-nano structured carbon fiber felt for liquid flow battery electrodes, which is prepared according to the above-mentioned method for preparing the micro-nano structured carbon fiber felt for liquid flow battery electrodes.

[0064] The present invention also provides an application of the above-mentioned micro-nano structure carbon fiber felt for liquid flow battery electrodes in liquid flow battery electrodes. The electrode made of micro-nano structure carbon fiber felt for liquid flow battery electrodes has a current density of 120mA / cm 2 When the energy efficiency is ≥83%, the voltage efficiency is ≥84%, and the coulombic efficiency is ≥97%; the electrodes made of micro-nanostructured carbon fiber felt for flow battery electrodes are at a current density of 200mA / cm 2 When the energy efficiency is ≥80%, the voltage efficiency is ≥81%, and the coulombic efficiency is ≥97%.

[0065] The micro-nanostructured carbon fiber felt for liquid flow battery electrodes, its preparation method and application of the present invention are further introduced below with reference to specific examples.

[0066] Example 1

[0067] The method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode of this embodiment adopts the following steps:

[0068] (1) Weigh polyacrylonitrile powder, nano-boron carbide and dimethylformamide in a weight ratio of 100:2:1000, add the polyacrylonitrile powder and nano-boron carbide into dimethylformamide, stir at 50°C until they are uniformly dissolved to form a spinning solution, and prepare boron-containing polyacrylonitrile nanofibers through a single-needle electrospinning device.

[0069] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 220° C. for 1.5 hours, and then subjected to an opening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 6 cm and a diameter of 200 nm.

[0070] (3) Weigh the boron-containing pre-oxidized nanofiber short filaments and polyacrylonitrile-based short chopped pre-oxidized filaments obtained in step (2) in a weight ratio of 50:50, mix, card, lay a net, and needle punch to obtain a micro-nanostructure pre-oxidized felt with a thickness of 3.2 mm.

[0071] (4) The micro-nanostructured pre-oxidized felt obtained in step (3) is carbonized for 2 h in a nitrogen atmosphere at 800°C, graphitized for 2 h in a nitrogen atmosphere at 2000°C, and activated for 1 h in a carbon dioxide atmosphere at 800°C to obtain a micro-nanostructured carbon fiber felt electrode with a thickness of 2.5 mm.

[0072] The prepared micro-nanostructured carbon fiber felt was cut into 6cm×6cm pieces as electrodes to assemble into a single cell for charge and discharge performance testing: at a current density of 120mA / cm 2 When the current density is increased to 200mA / cm 2When the power consumption is 2.04W, the energy efficiency is 82.3%, the voltage efficiency is 83.8%, and the coulombic efficiency is 98.2%.

[0073] Example 2

[0074] The method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode of this embodiment adopts the following steps:

[0075] (1) Weigh polyacrylonitrile powder, nano-boron nitride and dimethylacetamide in a weight ratio of 100:3:1200, add the polyacrylonitrile powder and nano-boron nitride into dimethylacetamide, stir at 60°C until they are uniformly dissolved to form a spinning solution, and prepare boron-containing polyacrylonitrile nanofibers through a multi-needle electrospinning device.

[0076] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 230° C. for 1 hour, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 7 cm and a diameter of 300 nm.

[0077] (3) Weigh the boron-containing pre-oxidized nanofiber short fibers, polyacrylonitrile-based short chopped pre-oxidized fibers, and asphalt-based short chopped pre-oxidized fibers obtained in step (2) in a weight ratio of 50:30:20, mix, card, lay a net, and needle punch to obtain a micro-nanostructure pre-oxidized felt with a thickness of 3.8 mm.

[0078] (4) The micro-nanostructured pre-oxidized felt obtained in step (3) is carbonized in a nitrogen atmosphere at 900°C for 1.5 h, graphitized in a nitrogen atmosphere at 2100°C for 2 h, and activated in a water vapor atmosphere at 700°C for 1.5 h to obtain a micro-nanostructured carbon fiber felt electrode with a thickness of 2.8 mm.

[0079] The prepared micro-nanostructured carbon fiber felt was cut into 6cm×6cm pieces as electrodes to assemble into a single cell for charge and discharge performance testing: at a current density of 120mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 83.2%, the voltage efficiency is 85.6%, and the coulombic efficiency is 97.2%.

[0080] Example 3

[0081] The method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode of this embodiment adopts the following steps:

[0082] (1) Weigh polyacrylonitrile powder, nano zirconium boride and dimethyl sulfoxide in a weight ratio of 100:3.5:1500, add the polyacrylonitrile powder and nano zirconium boride into dimethyl sulfoxide, stir at 55°C until they are uniformly dissolved to form a spinning solution, and prepare boron-containing polyacrylonitrile nanofibers through a needleless electrospinning device.

[0083] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 210° C. for 2 hours, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 7.5 cm and a diameter of 350 nm.

[0084] (3) Weigh the boron-containing pre-oxidized nanofiber short fibers, polyacrylonitrile-based short chopped pre-oxidized fibers, and asphalt-based short chopped pre-oxidized fibers obtained in step (2) in a weight ratio of 35:55:10, mix, card, lay a net, and needle punch to obtain a micro-nanostructure pre-oxidized felt with a thickness of 5.2 mm.

[0085] (4) The micro-nanostructured pre-oxidized felt obtained in step (3) is carbonized for 1.5 h in a nitrogen atmosphere at 850°C, graphitized for 2 h in a nitrogen atmosphere at 2200°C, and activated for 1 h in a carbon dioxide atmosphere at 900°C to obtain a micro-nanostructured carbon fiber felt electrode with a thickness of 4.0 mm.

[0086] The prepared micro-nanostructured carbon fiber felt was cut into 6cm×6cm pieces as electrodes to assemble into a single cell for charge and discharge performance testing: at a current density of 120mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 81.5%, the voltage efficiency is 83.1%, and the coulombic efficiency is 98.1%.

[0087] Example 4

[0088] The method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode of this embodiment adopts the following steps:

[0089] (1) Weigh polyacrylonitrile powder, nano-titanium boride and dimethylformamide in a weight ratio of 100:2:1600, add the polyacrylonitrile powder and nano-titanium boride into dimethylformamide, stir at 60°C until they are uniformly dissolved to form a spinning solution, and prepare boron-containing polyacrylonitrile nanofibers through a needleless electrospinning device.

[0090] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 230° C. for 1.5 hours, and then subjected to a loosening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 8 cm and a diameter of 320 nm.

[0091] (3) Weigh the boron-containing pre-oxidized nanofiber short fibers, polyacrylonitrile-based short chopped pre-oxidized fibers, and viscose-based short chopped pre-oxidized fibers obtained in step (2) in a weight ratio of 55:35:10, mix, card, lay a web, and needle punch to obtain a micro-nanostructure pre-oxidized felt with a thickness of 6.3 mm.

[0092] (4) The micro-nano structure pre-oxidized felt obtained in step (3) is carbonized for 2 h in a nitrogen atmosphere at 1000°C, graphitized for 1.5 h in a nitrogen atmosphere at 2300°C, and activated for 1.2 h in a carbon dioxide atmosphere at 950°C to obtain a micro-nano structure carbon fiber felt electrode with a thickness of 5.0 mm.

[0093] The prepared micro-nanostructured carbon fiber felt was cut into 6cm×6cm pieces as electrodes to assemble into a single cell for charge and discharge performance testing: at a current density of 120mA / cm 2 When the current density is increased to 200mA / cm 2 When the energy efficiency is 81.0%, the voltage efficiency is 82.5%, and the coulombic efficiency is 98.2%.

[0094] Example 5

[0095] The method for preparing a micro-nanostructured carbon fiber felt for a flow battery electrode of this embodiment adopts the following steps:

[0096] (1) Weighing polyacrylonitrile powder, nano-boron carbide and dimethylformamide in a weight ratio of 100:5:900, adding the polyacrylonitrile powder and nano-boron carbide into dimethylformamide, stirring at 60°C until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers through a single-needle electrospinning device.

[0097] (2) The boron-containing polyacrylonitrile nanofibers obtained in step (1) are subjected to a pre-oxidation treatment in an air atmosphere at 215° C. for 2 hours, and then subjected to an opening and interruption treatment to obtain boron-containing pre-oxidized nanofiber short filaments with a length of 7.5 cm and a diameter of 500 nm.

[0098] (3) Weigh the boron-containing pre-oxidized nanofiber short fibers and polyacrylonitrile-based short chopped pre-oxidized fibers obtained in step (2) at a weight ratio of 70:30, mix, card, lay a net, and needle punch to obtain a micro-nanostructure pre-oxidized felt with a thickness of 4.7 mm.

[0099] (4) The micro-nanostructured pre-oxidized felt obtained in step (3) is carbonized for 2 h in a nitrogen atmosphere at 1200°C, graphitized for 2 h in a nitrogen atmosphere at 2150°C, and activated for 2.5 h in a water vapor atmosphere at 800°C to obtain a micro-nanostructured carbon fiber felt electrode with a thickness of 3.5 mm.

[0100] The prepared micro-nanostructured carbon fiber felt was cut into 6cm×6cm pieces as electrodes to assemble into a single cell for charge and discharge performance testing: at a current density of 120mA / cm 2 When the current density is increased to 200mA / cm 2 When the power consumption is 2.5W, the energy efficiency is 80.5%, the voltage efficiency is 81.7%, and the coulombic efficiency is 98.5%.

[0101] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for preparing micro-nanostructured carbon fiber felt for flow battery electrodes, It is characterized in that The following steps are involved: S1, adding polyacrylonitrile powder and nano-boride into an organic solvent, stirring until uniformly dissolved to form a spinning solution, and preparing boron-containing polyacrylonitrile nanofibers by high-voltage electrospinning; S2, pre-oxidizing and opening and breaking the boron-containing polyacrylonitrile nanofibers to obtain boron-containing pre-oxidized nanofiber staples; S3, mixing, combing, laying and needle punching the boron-containing pre-oxidized nanofiber short filaments and short chopped pre-oxidized filaments to obtain a micro-nano structure pre-oxidized felt; S4, carbonizing, graphitizing and activating the micro-nano structured pre-oxidized felt to obtain a micro-nano structured carbon fiber felt.

2. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 1, It is characterized in that In step S1: The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.1-20):(500-3000); and / or The nano boride is selected from one or more of nano boron nitride, nano boron carbide, nano zirconium boride and nano titanium boride; and / or The organic solvent is selected from one of dimethylformamide, dimethyl sulfoxide and dimethylacetamide; and / or The stirring temperature is 30 to 90° C.; and / or The high-voltage electrospinning is one of single-needle, multi-needle and needle-free.

3. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 2, It is characterized in that In step S1: The weight ratio of the polyacrylonitrile powder, the nano boride and the organic solvent is 100:(0.5-10):(800-2000) and / or The stirring temperature is 40-80°C.

4. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 1, It is characterized in that In step S2: The pre-oxidation treatment is carried out in an air atmosphere at 180-300° C. for a treatment time of 0.5-5 h; and / or The boron-containing pre-oxidized nanofiber short filaments have a length of 3 to 12 cm and a diameter of 50 to 800 nm.

5. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 4, It is characterized in that In step S2: In the pre-oxidation treatment, the treatment temperature is 200-280° C. and the treatment time is 1-4 hours; and / or The boron-containing pre-oxidized nanofiber short filaments have a length of 5 to 9 cm and a diameter of 100 to 600 nm.

6. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 1, It is characterized in that In step S3: The weight ratio of the boron-containing pre-oxidized nanofiber short filaments to the short chopped pre-oxidized filaments is 10:90 to 90:10; and / or The chopped pre-oxidized yarn is selected from one or more of polyacrylonitrile-based pre-oxidized yarn, asphalt-based pre-oxidized yarn and viscose-based pre-oxidized yarn; and / or The thickness of the micro-nano structure pre-oxidation felt is 2 to 10 mm.

7. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 6, It is characterized in that In step S3: The weight ratio of the boron-containing pre-oxidized nanofiber short filaments to the short chopped pre-oxidized filaments is 20:80 to 80:20; and / or The thickness of the micro-nano structure pre-oxidation felt is 3-8 mm.

8. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 1, It is characterized in that In step S4: The carbonization process is carried out in a nitrogen atmosphere, the carbonization temperature is 600-1600° C., and the carbonization time is 0.5-4 h; and / or The graphitization process is carried out in a nitrogen atmosphere, the graphitization temperature is 1800-3000° C., and the graphitization time is 0.5-4 h; and / or The activation process is carried out in an activation gas atmosphere, the activation temperature is 500-1500° C., and the graphitization time is 0.5-5 h; and / or The thickness of the micro-nano structure carbon fiber felt is 1 to 8 mm.

9. The method for preparing the micro-nanostructured carbon fiber felt for flow battery electrodes according to claim 8, It is characterized in that In step S4: During the carbonization process, the carbonization temperature is 700-1500° C. and the carbonization time is 1-3 hours; and / or During the graphitization process, the graphitization temperature is 1900-2800° C., and the graphitization time is 1-3 hours; and / or During the activation process, the activation gas is carbon dioxide or water vapor, the activation temperature is 600-1200° C., and the graphitization time is 1-4 hours; and / or The thickness of the micro-nano structure carbon fiber felt is 2-6 mm.

10. A micro-nanostructured carbon fiber felt for liquid flow battery electrodes prepared according to the method for preparing micro-nanostructured carbon fiber felt for liquid flow battery electrodes according to any one of claims 1 to 9.

11. Use of the micro-nano structured carbon fiber felt for liquid flow battery electrodes prepared according to the method for preparing the micro-nano structured carbon fiber felt for liquid flow battery electrodes according to any one of claims 1 to 9 in liquid flow battery electrodes.

12. The use according to claim 11, Features: The flow battery electrode is made of micro-nanostructured carbon fiber felt at a current density of 120 mA / cm 2 When the energy efficiency is ≥83%, the voltage efficiency is ≥84%, and the coulombic efficiency is ≥97%; and / or The flow battery electrode is made of micro-nanostructured carbon fiber felt at a current density of 200 mA / cm 2 When the energy efficiency is ≥80%, the voltage efficiency is ≥81%, and the coulomb efficiency is ≥97%.

Citation Information

Patent Citations

  • Method for preparing electrode material for all-vanadium flow battery

    CN102522568A

  • Electrode material for all-vanadium redox flow battery and preparation and application thereof

    CN109841851A

  • Preparation method for boron-containing polyacrylonitrile protofilament and carbon fiber thereof and graphite fiber

    CN106917156A

  • A lithium battery separator in a high-strength fiber structure and a preparation method and application thereof

    CN109585751A

  • Electrode material for all-vanadium redox flow battery and preparation thereof and application thereof

    CN109671953A

Cited By

  • Carbon fiber felt as well as preparation method and application thereof

    CN120006443A